Експресіонізм в історико-літературному просторі України 20-х років ХХ століття (на прикладі творчості М. Бажана, М. Куліша, О. Турянського) - Яструбецька, Галина; Yastrubetska, Halyna (Східноєвропейський національний університет імені Лесі Українки, 2015)
У статті поставлено завдання доповнити сформовану за останнє десятиліття рецептивну парадигму українського літературного експресіонізму початку ХХ ст. Зроблено діахронний зріз для уточнення експресіоністичних ущільнень з урахуванням видового, родового й територіального критеріїв. Об’єкти дослідження вибрано з огляду на новизну ракурсу презентації творчості М. Бажана, М. Куліша, О. Турянського, уже ідентифікованих як узалежнені від експресіонізму. Збірку М. Бажана «17-й патруль» проаналізовано як близьку до лівоекспресіоністських засад з одночасними проявами автентичного експресіонізму. П’єсу М. Куліша «Вічний бунт» інтегровано в площину ком’юніонізму-активізму із зазначенням синтетичної природи драматургії митця. Твір О. Турянського «Поза межами болю» розглянуто крізь призму синтезу засадничо-інваріантних ознак імпресіонізму та експресіонізму.In the article the task is to complete already formed in the last decade the receptive paradigm of Ukrainian literary expressionism of the early 20th century. Taking into account the aspectual, ancestral and territorial criteria the expressionistic closures were defined. The objects of the research were chosen taking into account the novelty of presentation of aspect of Mykola Bazhan, Mykola Kulish and Osyp Turianskyi works. These authors were identified as such who had been involved in expressionistic stylistic tendencies. It is noted that in native literary and artistic use the term “expressionism” was first attested in Western Ukraine. It is mentioned that the director of the theater “Berezil” Les Kurbas had made the contribution to the expansion of horizons of comprehension the concept “style of play” as well as attracting and learning the principles of expressionistic doctrine by the national theater. Mykola Kulish appeared in the light of the ideological and aesthetic searches of joining up the theater “Berezil” as the author, who is familiar with the synthetic nature of the drama. The play has gained the advantage while the choice for the analysis primarily because of the dominance of expressionistic signs without director’s revising. “Vichnyi Bunt” was integrated in the area of communionism and activism with the reference to the typological connections with the works of E. Toller, L. Rubiner, J. Becher, G. Benn, G. Kaiser. The collection “17th Patrul” by Mykola Bazhan is close to the left-expressionistic concepts. The poetry of Mykola Bazhan of this period was in the process of searching and showed the correlation of activism with authentic expressionism. Such feature of the author’s lyrics as creation of sense on the level of the rhythm is defined that reinforces the irrational ferment of poetic substance. Rhythm plays the role of aesthetic universal of the author’s artistic conception. “Poza Mezhamy Boliu” by Osyp Tyrianskyi is shown from the perspective of the synthesis of prime and invariant features of impressionism and expressionism. The graphic element of the text structure renders the idea of silence, which is the component of the work’s psychologism. Moreover, visual (typographic) equivalent of the author’s intention is that area where two world outlook antagonistic and artistic systems such as impressionism and expressionism are crossed and cooperate with each other. The twenties of the 20th century is the time of ageing and formation of expressionism as a stylistic unit with clearly defined, recognizable, formalist and informative signs.
Expressionism in Historical and Literary Era of Ukraine in the Twenties of 20th Century (in Terms of Works of M. Bazhan, M. Kulish, O. Turianskyi)
Keywords: стиль; експресіонізм; ком’юніонізм; активізм; імпресіонізм; синтетизм; style; expressionism; communionism; activism; impressionism; synthetism